STUDI KRIYA TEKSTIL SULAMAN BAYANGAN PADA UMKM GUS FITRI DI PESISIR SELATAN - Salsha Billa Tarisa Putri; Heldi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the shadow embroidery (sulaman bayangan) textile craft produced by the Gus Fitri micro, small, and medium enterprise (MSME) in Barung-Barung Balantai, Pesisir Selatan Regency, West Sumatra. The research aims to identify and describe the forms and functions of the shadow embroidery products, and to analyze the techniques, production process, and business development of the enterprise. A descriptive qualitative method was used, with data gathered through observation, in-depth interviews, and documentation involving the owner, two craftswomen, and one customer selected through purposive and snowball sampling, then analyzed using the Miles and Huberman interactive model. The findings show that Gus Fitri produces prayer garments (mukena), traditional blouses (baju kurung), and shawls dominated by floral and Minangkabau motifs, which simultaneously fulfil physical, social, and cultural functions. The reverse-stitch (jahit terbalik) technique creates the signature shadow effect, and the enterprise has innovated by adding a raised-appliqué technique. Production runs through motif design, motif transfer, hand embroidery, and finishing stages, carried out manually by around forty craftswomen. Across three generations the business has diversified its products, expanded its workforce, received institutional coaching, and adopted digital marketing, while still facing constraints in skilled labour and promotion. The study concludes that Gus Fitri exemplifies how a traditional textile craft can be documented, sustained, and creatively developed within a contemporary market.